Efek Penambahan Antioksidan dan Demulsifier Secara Polimerisasi Pada Proses Penimbunan Diesel Fuel - Venriza, Oksil; Lestari, Ika Gita; Riesdiawan, Yudhistira (Talenta Publisher (Universitas Sumatera Utara), 2023)
B30 is an environmentally friendly fuel used for diesel engines. B30 is very easily contaminated with water sourced from the production process and raw materials from the B30. This water content causes corrosion and has an impact on landfilling. A demulsifier is a way to break down the B30 and water emulsion. In this study, the demulsifier used was acrylate-based and mixed with polar and non-polar solvents. The addition of a demulsifier with a volume of 2 mL, 5 mL, and 10 mL in the stockpiling process with variations of 2 hours, 4 hours, and 6 hours obtained an effect on the volume of water, where the volume of water increases with longer storage time. But the effectiveness of the demulsifier can be evaluated by potentiometrically measuring the water content and FTIR. The demulsifier that was made was also added with an antioxidant in the form of tertiary butylhydroquinone (TBHQ) with a concentration of 0.5 M and obtained more separate water layers than without the addition of TBHQ. To obtain the water content value after adding TBHQ, the coulometric and Fourier Transform Infra Red methods were used, which yielded higher results when compared to the absence of TBHQ. So that antioxidants and dimulsifiers have a positive effect on the process of storing diesel fuel.